Solar pump water heating controller / Muhamad Syafiq Ariff Mad Pazir & Muhammad Syafiq Mohamad Zamri - Mad Pazir, Muhamad Syafiq Ariff; Mohamad Zamri, Muhammad Syafiq (2015)
The solar pump water heating is used to heat the water by using solar energy and stored the hot water into the water tanks. This project need to flow the hot water from the solar panel into the hot water tank. This will be when the temperature of both solar panel and hot water tank reach the Differential temperature. Differential temperature is temperature were set to operates the solar pump to flow in and out the water. This prototype help to build a water heating system by using natural supply energy which are solar energy from the sun which can reduce environmental pollution and lowest the cost. Lower cost in this projects means that solar panel consumes solar energy which is a renewable type sources. The circuit was designed by using software Proteus 8.0. The design prototype circuit was fabricated by using veroboard and the output were measured .. The output is the motor which represented the solar pump functioned when the temperature of reached diffON which show the solar pump is pumping the water from solar panel to hot water tank and water flow into the solar panel from the supplies when the temperature diffOFF is reached.